Factors shaping the financial liquidity of farms Czynniki kształtujące płynność finansową gospodarstw rolnych - Anna Bieniasz (Journal of Agribusiness and Rural Development, 2008)
In the article an attempt was undertaken to determine power and direction of the influence of chosen factors on the level of farms financial liquidity at applying econometric methods. The study was based on EU agricultural accountancy system FADN. Constructed regression models showed, that factor most strongly shaping the level of the financial liquidity is a politicy of working capital management. Its conservative character, appointed through the longer cycle of obligations and the cycle of the working capital, in-deed reducies the risk of the financial liquidity.